Struggling women characters in Manju Kapur’s Difficult Daughters - SUBATHRA, R.; DHANALAKSHMI, D. (International Journal of Psychosocial Rehabilitation, 2024)
Manju Kapur is a well-known Indian woman novelist writing in English. She has brought a fresh perspective to Indian fiction, focusing on common issues faced by women, especially Indian women. Her novels often explore themes like marriage, family relationships, husband-wife dynamics, separation, and extramarital affairs.Marriage is a key theme in her works, and she portrays different aspects of it. Some characters marry due to social pressure, while others feel trapped in their marriages and eventually break free. There are also characters who face challenges but try to adjust and make their marriages work. Through her stories, Manju Kapur highlights the complexities of marriage and relationships in Indian society.